Hepatocyte Transplantation: Methods and Protocols - Stock, Peggy; Christ, Bruno (Methods in molecular biology, 2017)
Hepatocyte Transplantation in Special Populations: Clinical Use in Children -- Alternative Cell Sources to Adult Hepatocytes for Hepatic Cell Therapy -- Late Gestation Fetal Hepatocytes for Liver Repopulation in the Rat -- A Modified Protocol for the Isolation of Primary Human Hepatocytes with Improved Viability and Function from Normal and Diseased Human Liver -- Thy-1 (CD90)-positive Hepatic Progenitor Cells, Hepatoctyes and Non-parenchymal Liver Cells Isolated from Human Livers -- Propagation of Human Hepatocytes in uPA/SCID Mice: Producing Chimeric Mice with Humanized Liver -- Fetal Liver Stem/Progenitor Cell Transplantation: A Model to Study Tissue Mass Replacement and Cell-based Therapies -- Successful Engraftment of Human Hepatocytes in uPA-SCID and FRG® KO Mice -- Gunn rats as Surrogate Model For Evaluation Of Hepatocyte Transplantation-based Therapies of Crigler-Najjar Syndrome Type 1 -- Experimental Hepatocyte Transplantation in Pigs -- Demonstrating Potential of Cell Therapy for Wilson´s Disease with the Long‐Evans Cinnamon Rat Model -- Use of Thymidine Kinase Recombinant Adenovirus and Ganciclovir Mediated Mouse Liver Preconditioning for Hepatocyte Xenotransplantation -- Minimally Invasive Liver Preconditioning for Hepatocyte Transplantation in Rats -- Preclinical Swine Models for Monitoring of Hepatocyte Transplantation by MRI -- Deep Digging - Far Red Imaging for the Monitoring of Transplanted Hepatocytes in Rat -- Isolation of GMP grade Human Hepatocytes from Remnant Liver Tissue of Living Donor Liver Transplantation -- Isolation of Hepatocytes and Stellate Cells from a Single Piece of Human Liver -- Microencapsulation of Hepatocytes and Mesenchymal Stem Cells for Therapeutic Applications -- Alginate Encapsulation of Human Hepatocytes and Assessment of Microbeads -- Report on Liver Cell Transplantation Using Human Fetal Liver Cells -- Hepatocyte Transplantation in Children -- Creation of Three-Dimensional Liver Tissue Models from Experimental Images for Systems Medicine. .